Movement law of the threshing material in threshing and cleaning machine for plot-bred wheat - Dai, Fei; Song, Xuefeng; Shi, Ruijie; Guo, Wenjuan; Zhao, Yiming; Wang, Feng; Zhao, Wuyun (International Journal of Agricultural and Biological Engineering, 2022)
In order to clarify and enhance the work performance of the threshing and cleaning machine for plot-bred wheat and further reduce the grain retention in all working areas in the machine, in this study, a discrete element model for the threshing material of plot-bred wheat and a gas-solid coupling simulation model for the machine were established by ensuring all the harvesting criteria for the machine. Then numerical simulation was completed on the movement process of the threshing material in the threshing and cleaning machine for plot-bred wheat, the movement law and motion trajectory of all components of the threshing material were explored, and the impact forms of unreasonable work parameters on the separating and cleaning process were analyzed. First, four working areas were divided in the threshing and cleaning machine for plot-bred wheat. Under gas-solid flow coupling effect, the number variation of threshing material in each working area was analyzed under the effect of gas-solid coupling, and the operation characteristics of “no retained seeds and convenient cleaning” of the threshing machine for plot-bred wheat were further improved. The verification test results showed that, when the feeding amount of wheat was 0.30 kg/s, the rotation speed of the shaft of the tooth-type threshing cylinder was set to 1350 r/min, the rotation speed of the winnower was set to 500 r/min, the rotation speed of the residue absorption fan was set to 1000 r/min, the average total loss rate in threshing of the sample machine was 0.56%, and average impurity rate of the threshing material was 5.26%, average damage rate in threshing was 0.68%. In the test, the status of material discharged from the residue absorption fan outlet and bottom of the cyclone separator was similar to that of the simulation results, showing that it was feasible to use the method of gas-solid coupling to simulate the movement law of threshing material in the threshing and cleaning machine for plot-bred wheat.Keywords: plot-bred wheat, threshing and cleaning machine, computational fluid mechanics, discrete element, numerical simulation, testDOI: 10.25165/j.ijabe.20221503.7194Citation: Dai F, Song X F, Shi R J, Guo W J, Zhao Y M, Wang F, et al. Movement law of the threshing material in threshing and cleaning machine for plot-bred wheat. Int J Agric & Biol Eng, 2022; 15(3): 100–106.